Boosting ART uptake and retention among HIV‐infected pregnant and breastfeeding women and their infants: the promise of innovative service delivery models. Issue 1 (22nd January 2018) - Srivastava, Meena; Sullivan, David; Phelps, B. Ryan; Modi, Surbhi; Broyles, Laura N.
Abstract: Introduction: With the rapid scale‐up of antiretroviral treatment (ART) in the "Treat All" era, there has been increasing emphasis on using differentiated models of HIV service delivery. The gaps within the clinical cascade for mothers and their infants suggest that current service delivery models are not meeting families' needs and prompt re‐consideration of how services are provided. This article will explore considerations for differentiated care and encourage the ongoing increase of ART coverage through innovative strategies while also addressing the unique needs of mothers and infants. Discussion: Service delivery models should recognize that the timing of the mother's HIV diagnosis is a critical aspect of determining eligibility. Women newly diagnosed with HIV require a more intensive approach so that adequate counselling and monitoring of ART initiation and response can be provided. Women already on ART with evidence of virologic failure are also at high risk of transmitting HIV to their infants and require close follow‐up. However, women stable on ART with a suppressed viral load before conception have a very low likelihood of HIV transmission and thus are strong candidates for multi‐month ART dispensing, community‐based distribution of ART, adherence clubs, community adherence support groups and longer intervals between clinical visits. A number of other factors should be considered when defining eligibility of mothers and infants for differentiated care, including location of services, viral load monitoring and duration on ART. To provide differentiated care that is client‐centred and driven while encompassing a family‐based approach, it will be critical to engage mothers, families and communities in models that will optimize client satisfaction, retention in care and quality of services. Conclusions: Differentiated care for mothers and infants represents an opportunity to provide client‐centred care that reduces the burden on clients and health systems while improving the quality and uptake of services for families. However, with decreasing funding, stable HIV incidence, and aspirations for sustainability, it is critical to consider efficient, customized and cost‐effective models of care for these populations as we aspire to eliminate mother‐to‐child transmission of HIV.